Freaky [videorecording (DVD)] - Landon, Christopher, 1975-; Landon, Christopher, 1975-; Vaughn, Vince; Newton, Kathryn, 1997-; O'Connor, Celeste (Universal Pictures Home Entertainment, 2021)
A seventeen-year-old girl swaps bodies with a notorious serial killer and has only twenty-four hours to undo the change before it becomes permanent.